Petty justice : low law and the sessions system in Charlotte County, New Brunswick, 1785-1867 - Craven, Paul, 1950- (Osgoode Society for Canadian Legal History series., 2014)
Petty Justice examines the role of justices of the peace and other front-line low law officials like customs officers and deputy land surveyors in colonial local government.